Energy Balance and Blood Metabolites Status of Local Sheep Based on Indigofera sp and Sproutbean Waste Ration - D A Astuti; S Rahayu; K B Satoto; R Priyanto; L Khotijah; T Suryati; M Baihaqi (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2018)
This research was undertaken to evaluate energy utilization and blood metabolites status of male Indonesian local sheep involving nutrient balances and using urea space techniques for measurement body composition. Factorial randomized completely design was used in this study using 16 growing male local sheep. Factor A was breed which consisted of 8 Garut sheep (av.BW 14.90 kg) and 8 Jonggol sheep (av.BW 13.60 kg). Factor B was different ration which received of diet containing Indigoferasp. and sproutbean waste. The ration offered were pellets containing CP around 16% and energy 15.6 MJ GE kg-1. Energy balance and blood metabolites studies were conducted during three-months trial. Intake, digestibility, urinary and metabolism variables were measured based on total collection method. Methane energy was measured by rusitec technique and methane gas production multiplied by calory equivalent value of methane. Energy retention (RE) was measured by urea space technique. Heat production was calculated from ME-RE. Plasma glucose, cholesterol and urea-N were measured by using spectrophotometry. Results showed that there were significant differences of energy intakes, digestibilities and metabolism among the rations. Animals fed with sproutbean waste ration has higher energy utilization compared to those fed Indigofera sp ration. There were no significant different for all blood metabolite variables among breed and its interaction between combination treatments. It is concluded that sproutbean waste in local sheep ration has higher energy utilization and daily gain than Indigofera sp. Keywords: Indigofera sp., local sheep, rusitec technique, sproutbean, urea space